2019
DOI: 10.7717/peerj.8130
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral blood bovine lymphocytes and MAP show distinctly different proteome changes and immune pathways in host-pathogen interaction

Abstract: Mycobacterium avium subsp. paratuberculosis (MAP) is a pathogen causing paratuberculosis in cattle and small ruminants. During the long asymptomatic subclinical stage, high numbers of MAP are excreted and can be transmitted to food for human consumption, where they survive many of the standard techniques of food decontamination. Whether MAP is a human pathogen is currently under debate. The aim of this study was a better understanding of the host-pathogen response by analyzing the interaction of peripheral blo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 59 publications
0
6
0
Order By: Relevance
“…Analysis of peptides was performed as described [ 5 , 12 ]. Acidified eluted peptides were analyzed in the data-dependent mode on a Q Exactive HF mass spectrometer (Thermo Fisher Scientific, Bremen, Germany) online coupled to an UItimate 3000 RSLC nano-HPLC (Dionex, Sunnyvale, CA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Analysis of peptides was performed as described [ 5 , 12 ]. Acidified eluted peptides were analyzed in the data-dependent mode on a Q Exactive HF mass spectrometer (Thermo Fisher Scientific, Bremen, Germany) online coupled to an UItimate 3000 RSLC nano-HPLC (Dionex, Sunnyvale, CA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…In clinically infected cattle it causes weight loss, diarrhea, and reduced milk yields, and therefore causes major economic losses for the farmer [ 3 , 7 ]. After infection, ruminants usually go through a long, asymptomatic subclinical phase during which MAP cannot reliably be detected by standard diagnostic tests [ 8 , 9 ]. These infected but unrecognized animals are the major spreaders of the disease in livestock and remain difficult to identify because available diagnostic tests are not sensitive enough to detect them [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…On farms where natural MAP infections are detected, there are always differences in the susceptibility of some cattle to the infection. In a previous study, we showed that co-incubation of MAP and peripheral blood mononuclear cells (PBMC) from cows from a MAP-free farm with different immunophenotypes responded to co-incubation with MAP with increased abundance of proteins that can promote MAP infection and persistence [ 18 ], while a classical IL-12-driven immune response was observed in control cows [ 8 ]. On farms with established MAP occurrence, some cows were more susceptible to MAP infection than others [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…A good example for this environment-dependent variation are cell wall-deficient forms of MAP that were repeatedly isolated from human intestines [ 6 , 28 , 29 , 30 ]. In a previous study, we showed that after incubation of MAP with peripheral blood mononuclear cell (PBMC) of cows with different immunological phenotypes, the exoproteome of MAP changed according to the immunological phenotype of the leukocytes used for coincubation [ 31 ]. For milk, altered properties of MAP were shown by an in vitro experiment, in which incubation of MAP in milk led to faster translocation through a monolayer of Madin–Darby bovine kidney epithelial cells (MDBK) cells [ 32 ].…”
Section: Introductionmentioning
confidence: 99%